Does Biofloc Improve the Energy Distribution and Final Muscle Quality of Shrimp, Litopenaeus vannamei (Boone, 1883)?. Issue 2 (17th April 2018) - Chan‐Vivas, Elisa; Edén, Magaña‐Gallegos; Maldonado, Carlos; Escalante, Karla; Gaxiola, Gabriela; Cuzon, Gerard
Abstract: In a 45‐d experiment, Litopenaeus vannamei was cultured in two treatments, biofloc technology or clear water recirculating aquaculture system, to evaluate the effect on growth and survival, energy balance, and texture of the marketable product. The experimental design consisted of 40 plastic tanks of 54 L (20 tanks per treatment), with a density of 140 organisms/m 3 in each culture system. The final body weight, daily growth coefficient, and survival were significantly higher ( P < 0.05) in biofloc technology (12.40 g, 5.0%g/d, and 87.1%, respectively) than in the clear water system (7.0 g, 1.4%g/d, and 74.2%). The retained energy and energy content of exuviae were significantly higher for shrimp in the biofloc technology (448.5 ± 36.4 and 22.4 ± 1.8 J/shrimp/d, respectively) than in clear water (246.3 ± 40.9 and 12.3 ± 2.0 J/shrimp/d, respectively). Routine metabolism was significantly higher for the clear water treatment (411.4 ± 123.8 J/shrimp/d). Shear force was higher in the biofloc technology, indicating greater muscle firmness; this matched the gel electrophoresis patterns of the proteins extracted from the muscle tissues. This suggests that biofloc technology could be used not only to improve growth and survival in L. vannamei but also to enhance the final product quality and acceptability in the market.